78OImmunoscore predicts significant differences in time to recurrence in stage I colon cancer patients. (24th November 2019) - Galon, J; Hermitte, F; Mlecnik, B; Marliot, F; Bifulco, C; Lugli, A; Nagtegaal, I; Hartmann, A; van den Eynde, M; Roehrl, M; Ohashi, P; Zavadova, E; et al.
Abstract: Background: Immunoscore® is an in vitro diagnostic test that predicts the risk of relapse in patients with Colon Cancer (CC) by measuring the host immune response at the tumor site. It is an immune risk-assessment tool providing independent and superior prognostic value than traditional histopathological risk parameters, and is intended to be used as an adjunct to the TNM classification. Currently, Immunoscore plays a critical role to guide post-surgery decisions in stage II & III CC patients. In stage I, survival rates are high and adjuvant chemotherapy is not typically recommended. However, approximately 10% of stage I CC tumors will recur even after surgical resection. Methods: A subgroup analysis was performed on the stage I patients (n = 451) from the Immunoscore international validation study (Pagès et al. The Lancet 2018). Patients were classified by Immunoscore based on pre-defined cutoffs, either in 5 (IS 0-4) or in 3 categories: IS Low (IS0-1), Intermediate (IS 2), High (IS 3-4). Time to recurrence (TTR) was compared between Immunoscore categories. Results: Immunoscore Low, Intermediate and High were observed in 14%, 47% and 39% of the cohort, respectively. Immunoscore was positively and significantly correlated with TTR. When adjusting the model with Immunoscore, age, gender, T-stage sidedness and MSI, Immunoscore remained the sole significant parameter (stratified by participating center HRlow vs high =7.82; 95% CI 1.49 − 41.01; p = 0.015). In multivariate analysis, the variable with the most important relative contribution to the risk (Chi2) was Immunoscore. The robust correlation between Immunoscore classification and TTR was further corroborated by a separate analysis of the same cohort distributed into five IS categories. In MSS stage I patients, TTR rates at 5 years were 100%, 98.1%, 93.5%, 85.4%, 87.5% for IS4, IS3, IS2, IS1, IS0, respectively. Conclusions: Immunoscore® is a robust prognostic indicator of the risk of recurrence in stage I CC. This risk assessment tool reliably identifies a sub-group of patients with an increased risk of relapse for whom a more intensive surveillance program after curative resection may be recommended. Legal entity responsible for the study: SITC (Society for ImmunoTherapy of Cancer) / INSERM. Funding: Grants from National Institute of Health and Medical Research (INSERM), the LabEx Immuno-oncology, the Transcan ERAnet European project, Association pour la Recherche contre le Cancer, CARPEM, AP-HP, INCA translationnel, Japan-AMED (P-DIRECT) and MEXT (Grants-in-aid for Scientific Research-S), and Ministry of Health of the Czech Republic (AZV CR 15-28188A) Progres Q25-LF1. Disclosure: J. Galon: Advisory / Consultancy, Shareholder / Stockholder / Stock options, Co-founder : HalioDx; Research grant / Funding (institution): Perkin-Elmer; Advisory / Consultancy, Research grant / Funding (institution): IObiotech; Advisory / Consultancy, Research grant / Funding (institution): MedImmune; Research grant / Funding (institution): Janssen; Advisory / Consultancy, Research grant / Funding (institution): AstraZeneca; Research grant / Funding (institution): Imcheck Therapeutics; Advisory / Consultancy: BMS; Advisory / Consultancy: Northwest Biotherapeutics; Advisory / Consultancy: Amgen; Advisory / Consultancy: Gilead; Advisory / Consultancy: CatalYm GmbH; Advisory / Consultancy: Sanofi; Licensing / Royalties, Patent holder: INSERM. F. Hermitte: Shareholder / Stockholder / Stock options, Full / Part-time employment, Co-founder : HalioDx. B. Mlecnik: Licensing / Royalties, Patent holder: INSERM. F. Pagès: Licensing / Royalties, Patent holder: INSERM. All other authors have declared no conflicts of interest.